Fenofibrate Nanocrystal Composite Microparticles for Intestine-Specific Oral Drug Delivery System - Bhavesh D. Kevadiya; Liang Chen; Lu Zhang; Midhun B. Thomas; Rajesh N. Davé (MDPI AG, 2019)
Hydrophobic drug nanocrystals (NCs) manufactured by particle engineering have been extensively investigated for enhanced oral bioavailability and therapeutic effectiveness. However, there are significant drawbacks, including fast dissolution of the nanocrystals in the gastric environment, leading to physicochemical instability. To solves this issue, we developed an innovative technique that involves the encapsulation of nanocrystals in composite spherical microparticles (NCSMs). Fenofibrate (FNB) NCs (FNB-NCs) manufactured by a wet stirred media milling (WSMM) technique and an ionotropic crosslinking method were used for FNB-NC encapsulation within gastroresistant NCSMs. Various solid-state methods were used for characterizing NCSMs. The pH-sensitive NCSMs showed a site-specific release pattern at alkaline pH and nearly 0% release at low pH (gastric environment). This phenomenon was confirmed by a real-time in situ UV-imaging system known as the surface dissolution imager (SDI), which was used to monitor drug release events by measuring the color intensity and concentration gradient formation. All these results proved that our NCSM approach is an innovative idea in oral drug delivery systems, as it resolves significant challenges in the intestine-specific release of hydrophobic drugs while avoiding fast dissolution or burst release.